Urine as an important source of sodium increases decomposition in an inland but not coastal tropical forest - Donoso Vargas, D. (2015)
Nutrient pulses can profoundly impact ecosystem processes and urine is a frequently deposited source of N and K, and Na. Na is unimportant to plants, but its addition can increase decomposition and change invertebrate community structure in Na-poor tropical forests. Here we used synthetic urine to separate the effects of Na from urines other nutrients and contrasted their roles in promoting decomposition and detritivore recruitment in both a Na-poor inland Ecuadorian and Na-rich coastal Panamanian tropical forest. After 2 days, invertebrate communities did not vary among +Na, H2O, Urine+Na, and Urine?Na treatments. But after 2 weeks, Ecuador wood, but not cellulose, decomposition was twofold higher on Urine+Na and +Na plots compared to H2O and Urine?Na plots accompanied by >20-fold increases in termite abundance on these plots. Panama, in contrast, showed no effect of Na on decomposition. In both forests, plots fertilized with urine had nearly twofold decrease in detritivores after 2 weeks that was likely a shock effect from ammonification. Moreover, the non-Na nutrients in urine did not enhance decomposition at this time scale. On control plots, Panama had higher decomposition rates for both cellulose and wood than Ecuador, but the addition of Na in Ecuador alleviated these differences. These results support the hypothesis that in Na-poor tropical forests, urine can enhance wood decomposition and generate an important source of heterogeneity in the abundance and activity of brown food webs.